In situ formation of MoS2/C nanocomposite as an anode for high-performance lithium-ion batteries. Issue 95 (27th September 2016) - Lee, Gyu-Ho; Kim, Si-Jin; Kim, Min-Cheol; Choe, Hui-Seon; Kim, Da-Mi; Han, Sang-Beom; Kwak, Da-Hee; Jeong, Jae Hyun; Park, Kyung-Won
Abstract : Anode materials with excellent electrochemical properties as an alternative to carbon-based structures are suggested for advanced high-performance lithium-ion batteries. Abstract : Anode materials with excellent electrochemical properties as an alternative to carbon-based structures are suggested for advanced high-performance lithium-ion batteries. Here, composites containing MoS2 and carbon (MoS2 /C) were in situ synthesized via heat treatment at 700 °C under a CH4 atmosphere with varying reaction times. XRD, Raman, XPS, and TEM data show that the MoS2 /C composites consist of crystalline MoS2 and an amorphous carbon phase and show a homogeneous distribution of curved and bent MoS2 particles with a carbon matrix. In particular, the MoS2 /C composite with an optimal content of the amorphous carbon phase exhibits relatively an excellent performance in lithium-ion batteries, facilitating the lithiation/delithiation process in MoS2 as an electroactive material.